Living Conditions and Social Outcomes in Adults With Cerebral Palsy - Pettersson, Katina; Rodby-Bousquet, Elisabet (Frontiers in Neurology, 2021)
Objectives: To analyse the living conditions and social outcomes (housing, engagement in employment or higher education, access to personal assistance and having a partner) in adults with cerebral palsy (CP) relative to their age, sex, communication ability, and motor skills. Methods: Cross-sectional registry-based study of 1,888 adults (1,030 males/858 females) with CP in the Swedish CP follow-up programme, median age 25 years (range 16–78 y). Type of housing, occupation, access to personal assistance and having a partner were analysed relative to their age, sex, and the classification systems for Gross Motor Function (GMFCS) and Communication Function (CFCS). Binary logistic regression models were used to calculate odds ratios (OR) for independent living, competitive employment, and having a partner. Results: Most of the 25- to 29-year olds (55.6%) lived independently, increasing to 72.4% in 40- to 49-year olds, while the majority (91.3%) of those under 20 years lived with their parents. Independent living was almost equal in adults at GMFCS levels I (40.2%) and V (38.6%). This parity was explained by access to personal assistance, which increased with higher GMFCS and CFCS levels. Personal assistance of >160 hours/week was associated with a high probability of independent living (OR 57). In the age span 20–64 years, 17.5% had competitive employment and 45.2% attended activity centres for people with intellectual disabilities. In the younger age group up to 24 years old, 36.9% went to mainstream/higher education and 20.5% went to special schools. In total, 13.4% had a partner and 7.8% lived together. Slightly more women than men had a partner, and most individuals were classified at CFCS level I. Conclusion: Only one in eight adults with CP has a partner, and one in six has competitive employment. Access to personal assistance is the single most important factor for independent living. It is vital to support adults with CP throughout their lifespan to achieve the best possible outcomes in all aspects of life.